Characterization of white-alcatraz producers in La Perla, Veracruz - Trejo-Téllez Brenda I.; Torres-Flores, Nadia I.; Trejo-Téllez Libia I. (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the white alcatraz (Zantedeschia aethiopica (L) K. Spreng) is considered a minor crop of cut f lowers grown in the central region of the state of Veracruz. The aim of this study was to determine the status of the producers of alcatraz in the town of La Perla, Veracruz. The research method consisted of a survey by a questionnaire sent to a representative sample of producers in this county alcatraz. The results show that 53% of producers are people who have low levels of schooling, see no need to belong to an association, more than 80% of farmers consider it a very profitable business; have become associated with other plants alcatraz to strengthen their economy. Ongoing training on agronomic crop management is recommended to provide a comprehensive management plants, focus to combat and eradicate "soft rot", the main phytosanitary problem, coupled with the traditional system of production, lack of investment and value addition.